The Role of Artificial Intelligence in the Audit Process and How to Fraud Detections: A Literature Outlook - SAIFUDIN, Saifudin; Januarti, Indira; Purwanto, Agus (Journal of Ecohumanism, 2025)
This study is aimed to test the role of artificial intelligence in the audit process and how artificial intelligence plays a role in detecting fraud using a literature review approach. The method used in this study is a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method, with an observation period of 32 years from 1992 to 2024. 101 articles were obtained, but only 15 articles were eligible. Of the fifteen articles, it shows that the article from Omoteso (2012) with the highest number of citations, i.e. 253 citations and the article with the least number of citations is the study of Qatawneh (2024). The domains used range from finance, accounting, auditing and also information systems. The limitations of this study are that it was only able to obtain fifteen articles through the PRISMA diagram process. For future research, it is expected to expand the study with the implications of using ATLAS Auditing for fraud prevention and combined with artificial intelligence.